DESIGN OF DIGITAL SHOE BASED SHOES SKIN MODELING AND CUTTING MACHINE - Dita Trisna Panjaitan; Jeksen Kristian Sinaga; Nurul Qodri; Vianola Elisa Karo Sekali; Fatuan Arif Sitorus; Rita Juliani (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2019)
Bunut is one of regions in Kisaran. The majority of Asahan District work as shoe craftsmen. The length time of shoes making procces make the shoe craftsmen need long time to market it. Similarly when designing shoe model that still us traditional tools that make shoe’s model impressed outdated. In terms of making Bunut shoe is not easy. Cutting leather shoe that use traditional tools make the cutting process of the shoe becomes long. The method is started from designing a modeling tool, preparing tools and material, making and testing machines. The result obtained by this shoe modeling machine work optimally 8 hours per day with the cutting velocity 1,4 minutes for each shoe's pattern, from the result modelling machine able to cut design pattern a pair of shoes in 40 minutes. So in one day it can produce shoe pattern pieces is able to produce 12 pairs of shoe patterns from the previous one, only 2 pairs per day.